Mechanobiological Assessment of TMJ Disc Surfaces: Nanoindentation and Transmission Electron Microscopy - Cassandra M. Juran; M. Franklin Dolwick; Peter S. McFetridge (Stilus Optimus, 2015)
Objectives: Temporomandibular disc is a mechanically robust fibrocartilage tissue exhibiting highly elastic compressive, shear, and tensile moduli with structurally dense extracellular matrix that supports functional loading of the joint. The aim of this study was to illustrate structural complexities of the superior and inferior disc surfaces, to demonstrate the robust mechanical ability of the disc as a whole may be due to depth-dependent regional/layered variation, and also to provide characterization data imperative for future tissue engineering efforts focused on restoring function to the joint. Material and Methods: Nanoindentation was used to assess tissue zones in conjunction with detailed Transmission Electron Microscopy to define structural attributes that influence the temporomandibular disc function. Results: The disc architecture adjacent to the superior surface was shown to have three distinct regional segments within the interface layer: 1-a surface peripheral layer; 2-subsurface region; and 3-a layer of helical matrix bundles. The inferior surface displayed an interface layer (20 µm) that showed limited cell populations with little depth-dependent structural variation, a stiffer elastic modulus and reduced energy dissipation compared to the superior surface. These data indicate that the primary function of the inferior surface is resistance to compression rather than load distribution during joint motion. Conclusions: These are the first works that demonstrate that the superior central surface of the he temporomandibular disc is structured in depth-dependent isometric layers, each of which provides different mechanical function supporting the bulk tissue's properties. From a clinical perspective these data have potential to define regions susceptible to fatigue that may translate to diagnostic criteria to better define the stages of dysfunction.